MEMORY LOSS IN AGING: WHAT’S NORMAL AND WHAT’S NOT - Mahakian , J. L. (Modern Psychology, 2019)
Alzheimer’s Care Armenia (www.alzheimerscarearmenia.org) is a nonprofit organization at the forefront of creating sustainable programs and services for people with memory loss and their families in Armenia. In this article, what is normal and not normal memory loss in aging will be discussed. People with age related memory loss have more generalized cognitive slowing and can live independently. Those with Mild Cognitive Impairment, which can progress to a dementia eventually, will need oversight and care. Providing education and information on memory loss and dementia to the community at large in Armenia is critical to raising awareness and visibility. Understanding what is normal and not normal memory loss has implications that could affect future screening, diagnosis and treatment.